Rotational Fasciocutaneous Flap-A Rescue Technique for exposed Tibia bone. (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the outcome of local rotational fasciocutaneus flap in the treatment of exposed tibia bone.Methods: We conducted this descriptive study in Department of Orthopedic surgery Liaquat University of Medical and Health Sciences, Jamshoro in collaboration with department of plastic surgery Liaquat University of Medical and Health Sciences, Jamshoro from 3rd January 2017 to 3rd June 2020. Patients of either gender and age with open tibia fractures and skin loss meeting the inclusion criteria were enrolled in our study. All patients were operated for fracture stabilization and coverage of the skin defect with rotational fasciocutaneous flap. Flap survival was assessed and results were graded as good, fair and failure as per Ponten criteria.Results: In this study 23 patients were included. Majority (78.26%, n=18) were males while females were 5(21.73%). Mean age was 31.8±9(range 18 to 46 years). Right tibia was involved in 14(60.8%) and left in 9(39.1) patients. Skin loss involved middle third of tibia was in 12(52.1%) patients, proximal third in 5(21.7%), distal third in 3(13%) and skin loss extended from middle to distal third in 3(13%) patients. The length of the flap varied from 9cm to 19 cm while the width varied from 3.5 cm to 9.5 cm. Flap survival results were good in 20(86.9%) patients and fair in 3(13%) patients. No flap failure was noted.Conclusion: Tibia fracture with skin loss treated with local rotational fasciocutaneus flaps produced good and fair outcome results without any flap failure in our series. We therefore recommend local rotational fasciocutaneus flap a technique of choice for coverage of variable tibia skin loss with fractures.